2020
DOI: 10.1186/s13613-020-00753-w
|View full text |Cite
|
Sign up to set email alerts
|

pCLIF-SOFA is a reliable outcome prognostication score of critically ill children with cirrhosis: an ESPNIC multicentre study

Abstract: Background and aims Data on outcome of critically ill children with cirrhosis are scarce. We aimed to evaluate the prognostic accuracy of sequential organs scoring systems in children with cirrhosis admitted to Paediatric Intensive Care Units (PICU). Methods We performed a multicentre retrospective analysis of children with cirrhosis admitted into four European PICUs between 2011 and 2016. Investigators were members of the ESPNIC liver failure and support working group. Paediatric End-Stage Liver Disease (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Several recent studies have identified that other scoring systems, which include detailed characterization of organ failures in children with cirrhosis, are more successful in predicting mortality in children when compared with MELD/PELD. [5,19] Specifically, the pediatric chronic liver failure sequential organ failure assessment score, which has specific criteria that define degrees of organ failure based on laboratory values, has an improved sensitivity (94.9%) and specificity (91.5%) in predicting 28-day mortality as compared with PELD. [5,19] Mataya et al [11] suggest a policy change for pediatric patients to "stratify children within the Status 1B priority group and prioritize those with ACLF over non-ACLF".…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have identified that other scoring systems, which include detailed characterization of organ failures in children with cirrhosis, are more successful in predicting mortality in children when compared with MELD/PELD. [5,19] Specifically, the pediatric chronic liver failure sequential organ failure assessment score, which has specific criteria that define degrees of organ failure based on laboratory values, has an improved sensitivity (94.9%) and specificity (91.5%) in predicting 28-day mortality as compared with PELD. [5,19] Mataya et al [11] suggest a policy change for pediatric patients to "stratify children within the Status 1B priority group and prioritize those with ACLF over non-ACLF".…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies reported information on the predictive capability of age-adapted pSOFA scores, 8e18 six studies reported on SIRS, 1,8,13,17e19 and four studies reported on qSOFA. 13,14,19,20,21 Concerning geographic distribution, five studies were conducted in China, 8,11,12,14,18 two in the UK 19,20 and South Korea, 22,23 one multicentric (Canada, USA and Uganda), 1 and one each was conducted in India, 9 Egypt, 10 Australia, 13 Europe, 15 Iran, 16 and Indonesia 17 (Table 1). The description of scoring system is shown in Supplementary Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…19 Other studies have also found that ACLF accounted for nearly 18% of patients with liver cirrhosis admitted to the paediatric intensive care unit. 20 In the adult population, the incidence of ACLF similarly differs based on the definition used. A study of 72,316 patients with decompensated cirrhosis has shown that the prevalence of ACLF was 26.4% and 9.8% based on the European and North American definitions, respectively.…”
Section: Epidemiologymentioning
confidence: 99%
“…30 Claude et al also showed that a pCLIF-SOFA score of >9 was predictive of mortality within 28 days with a sensitivity of 87.8% and a specificity of 77.3%, while a pCLIF-SOFA score of >7 was associated with increased odds of liver transplantation on day-60. 20 Lal et al 24 evaluated the APASL ACLF Research Consortium (AARC) acute-on-chronic liver failure (AARC-ACLF) score and its paediatricadapted version (Table 2) in prognosticating ACLF in children. The authors found that AARC-ACLF and CLIF-SOFA scores were superior to other prognostic scores in paediatric ACLF, and paediatric modifications of AARC-ACLF and CLIF-SOFA did not perform better than their original scores, all having AUROC of greater than 0.9 for predicting poor outcome in paediatric ACLF.…”
Section: Outcome and Prognostic Scoresmentioning
confidence: 99%